Improving health and reducing absence days at work: effects of a mindfulness- and skill-based leadership intervention on supervisor and employee sick days - Vonderlin, Ruben; Schmidt, Burkhard; Biermann, Miriam; Lyssenko, Lisa; Heinzel-Gutenbrunner, Monika; Kleindienst, Nikolaus; Bohus, Martin; Müller, Gerhard (Mindfulness, 2023)
Mindfulness-based programs (MBPs) at the workplace have attracted increasing interest due to their positive effects on health and work-related outcomes. However, it is unclear whether these effects translate into reductions in cost-related and objectively assessed outcomes, such as sick days. The aim of this study was to evaluate the effectiveness of an MBP for supervisors on reduction of sick days of both supervisors and their employees.